PAKET WISATA KAMPUNG BANDAR WALK HERITAGE KOTA PEKANBARU PROVINSI RIAU - Pasaribu, Rosmelisa; Sulistyani, Andri (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2019)
Kampung Bandar was a forerunner of founding the Pekanbaru city. Therefore, there is cultural heritage in Kampung Bandar and being tourism destination in Pekanbaru. This study being used to identify the cultural heritage in Kampung Bandar and creating tour package to explore cultural heritage of Kampung Bandar. The research was used qualitative method and descriptive approach. The subject of this research is Village of Kampung Bandar, tourism conscious group (pokdarwis), tourist village organization. The data collection techniques by observation, study document, interview and documentation. The data analysis technique by the reduction of data, presentation of data, and withdrawal of conclusion. The result of this research is Kampung Bandar has cultural attaction that is Rumah Tuan Kadi, Terminal Lama, Rumah Tenun Kampung Bandar, Kampung Melayu, Komplek Makam Marhum Pekan, Mesjid Raya Pekanbaru, Istana Hinggap, Roemah Melayoe 1929, Surau Al-Irhaash. The natural attraction is Sungai Siak and artificial atrraction is loak market. The easy accessibility with good enough road condition. There are amenities in Kampung Bandar and this tour handled by local guide. There was two tour packages offered to explore cultural heritage of Kampung Bandar were one day tour package with price is Rp. 230.000,- and two days one night tour package with price is Rp. 500.000,-.Keywords : Tour Packages, Cultural Heritage, Kampung Bandar